The Direct Torque Control (DTC) of the Permanent Magnet Synchronous Motor (PMSM) based on the nonsingular terminal sliding mode (NTSM) - Cheng, Ling; Wang, Zhao; Sun, Bing (2012 International Conference on Modelling, Identification and Control, 2012)
On the basis of the mathematical model of the PMSM, combining with the terminal sliding mode technology and DTC, the author has put forward the system of the DTC of the PMSM based on the NTSM which aims at solving such problems as the large ripple on flux linkage and torque, the difficulty of the precise control at a low speed of PMSM by DTC. In comparison with the traditional PI control, the NTSM can restrain itself in limited time and displays strong robustness to system parameters and outside interference. The singular phenomenon occurred in the terminal sliding mode is avoided through the adoption of the controller, and buffet which is common in regular sliding control is weaken. Therefore, the controlling effect of the whole system is improved considerably.